Structure of human complement C8, a precursor to membrane attack - Bubeck, D; Roversi, P; Donev, R; Morgan, B; Llorca, O; Lea, S (2011)
Complement component C8 plays a pivotal role in the formation of the membrane attack complex (MAC), an important antibacterial immune effector. C8 initiates membrane penetration and coordinates MAC pore formation. High-resolution structures of C8 subunits have provided some insight into the function of the C8 heterotrimer; however, there is no structural information describing how the intersubunit organization facilitates MAC assembly. We have determined the structure of C8 by electron microscopy and fitted the C8α-MACPF (membrane attack complex/perforin)-C8γ co-crystal structure and a homology model for C8β-MACPF into the density. Here, we demonstrate that both the C8γ protrusion and the C8α-MACPF region that inserts into the membrane upon activation are accessible. © 2010 Elsevier Ltd. All rights reserved.